IL-1 and senescence: Friends and foe of EGFR neutralization and immunotherapy - Romaniello, Donatella; Gelfo, Valerio; Pagano, Federica; Sgarzi, Michela; Morselli, Alessandra; Girone, Cinzia; Filippini, Daria Maria; D’Uva, Gabriele; Lauriola, Mattia (Frontiers in Cell and Developmental Biology, 2023)
Historically, senescence has been considered a safe program in response to multiple stresses in which cells undergo irreversible growth arrest. This process is characterized by morphological and metabolic changes, heterochromatin formation, and secretion of inflammatory components, known as senescence-associated secretory phenotype (SASP). However, recent reports demonstrated that anti-cancer therapy itself can stimulate a senescence response in tumor cells, the so-called therapy-induced senescence (TIS), which may represent a temporary bypass pathway that promotes drug resistance. In this context, several studies have shown that EGFR blockage, by TKIs or moAbs, promotes TIS by increasing IL-1 cytokine production, thus pushing cells into a “pseudo-senescent” state. Today, senotherapeutic agents are emerging as a potential strategy in cancer treatment thanks to their dual role in annihilating senescent cells and simultaneously preventing their awakening into a resistant and aggressive form. Here, we summarize classic and recent findings about the cellular processes driving senescence and SASP, and we provide a state-of-the-art of the anti-cancer strategies available so far that exploits the activation and/or blockade of senescence-based mechanisms.